The role of parenting patterns in early childhood emotional regulation in the digital era - Amali, Nailul; Hikmah, Fitrotul (Universitas Islam Malang, 2025)
The digital era introduces challenges to the emotional development of young children as a result of heightened media exposure. Parents significantly influence the regulation of their child's emotions. The parenting style significantly influences this issue. This study seeks to examine the different parenting styles that affect children's emotional development. This study employs a literature review methodology. The literature database was accessed via Google Scholar. Data were gathered through literature searches using the terms